Application of the Stochastic Markov Model in Predicting the Volume of Oil Spill in Nigeria: A Case of the Niger-delta Region - Mba, Ifeoma Christy; Mba, Emmanuel Ikechukwu; Arazu, Winnie Ogonna; URAMA, CHINASA E.; Machebe, Chioma Henrietta; Eze, Chikodili (International Journal of Energy Economics and Policy, 2019)
Oil spillage in the Niger Delta region of Nigeria and its associated hazard is on the increase and there is urgent need to combat its increasing volume by predicting the volume in the future thus, the objective of this study is on the prediction of the volume of oil spill in Nigeria via the Stochastic Markov Model. Two States Markov analysis were employed and it was discovered that the volume of oil spill incident were mostly maintained in a high state than in a low state and the predicted values were approximately steady at a probability value of 0.519 which is in favour of the high state. The study concluded that for the Nigerian Federal government to combat the volume of oil spill, she should in addition to enforcing the laws governing the volume of oil spill incident, employ remediation process that would help clean up the mess caused the spillage. Keywords: occurrence, oil spill, Niger Delta JEL Classifications: P28, Q53, Q56 DOI: https://doi.org/10.32479/ijeep.7744